Kappa-light Chain Amyloid Overlapping Hypertrophic Cardiomyopathy With Myocardial Noncompaction. (July 2020) - Frustaci, Andrea; Galea, Nicola; Verardo, Romina; Francone, Marco; Alfarano, Maria; Russo, Matteo Antonio; Chimenti, Cristina
Abstract : Supplemental Digital Content is available in the text.